Pairwise toxicity evaluation of ceramic nanoparticles in submerged and air-liquid interface cultures of human alveolar epithelial A549 cells - Bessa, Maria João (2019)
Objectives: To investigate the in vitro toxicity of ceramic NPs (CeO2, ZrO2 and Sb2O3•SnO2 NPs) in human alveolar epithelial cells, a primary target during inhalation exposure, in both submerged and air-liquid cell cultures